Quantification of Cold-Ion Beams in a Magnetic Reconnection Jet - Li, Yu-Xuan; Li, Wen-Ya; Tang, Bin-Bin; Norgren, C.; He, Jian-Sen; Wang, Chi; Zong, Qiu-Gang; Toledo-Redondo, S.; André, M.; Chappell, C.; Dargent, J.; Fuselier, S. A.; et al. (Frontiers in Astronomy and Space Sciences, 2021)
Cold (few eV) ions of ionospheric origin are widely observed in the lobe region of Earth's magnetotail and can enter the ion jet region after magnetic reconnection is triggered in the magnetotail. Here, we investigate a magnetotail crossing with cold ions in one tailward and two earthward ion jets observed by the Magnetospheric Multiscale (MMS) constellation of spacecraft. Cold ions co-existing with hot plasma-sheet ions form types of ion velocity distribution functions (VDFs) in the three jets. In one earthward jet, MMS observe cold-ion beams with large velocities parallel to the magnetic fields, and we perform quantitative analysis on the ion VDFs in this jet. The cold ions, together with the hot ions, are reconnection outflow ions and are a minor population in terms of number density inside this jet. The average bulk speed of the cold-ion beams is approximately 38% larger than that of the hot plasma-sheet ions. The cold-ion beams inside the explored jet are about one order of magnitude colder than the hot plasma-sheet ions. These cold-ion beams could be accelerated by the Hall electric field in the cold ion diffusion region and the shrinking magnetic field lines through the Fermi effect.